Eosinophils at diagnosis are elevated in amyotrophic lateral sclerosis - Yang, Jing; Liu, Tingting; Zhang, Lei; Li, Xin; Du, Feng Ping; Liu, Qi; Dong, Hui; Liu, Yaling (Frontiers in Neurology, 2023)
Introduction: Amyotrophic lateral sclerosis (ALS) is a rare, devastating neurodegenerative disease that affects upper and lower motor neurons. To date, no effective treatment or reliable biomarker for ALS has been developed. In recent years, many factors have been proposed as possible biomarkers of ALS; however, no consensus has been reached. Therefore, reliable biomarker is urgently needed. Eosinophils may play a crucial role in healthy humans and diseases, and serve as a biomarker for many chronic diseases. Methods: Routine blood test results were collected from 66 healthy controls and 59 patients with ALS. The percentages and total numbers of each cell population were analyzed, and the correlation between these indicators and patient ALS Functional Rating Scale–Revised (ALSFRS-R) score or disease progression rate (ΔFS score) were analyzed. Results: Compared to healthy controls, the number of blood leukocytes, neutrophils, monocytes and basophils was significantly decreased in ALS patients (p=0.002, p=0.001, p=0.049, p<0.0001, respectively). There was an increase in the number of eosinophils (p<0.0001), but no difference in the number of lymphocytes between ALS patients and healthy controls was found (p=0.563). Compared to healthy controls, the percentage of neutrophils was decreased and the percentage of lymphocytes and eosinophils was increased in ALS patients (p=0.01, p=0.012, p=0.001, respectively). There was no difference between ALS patients and healthy controls in the percentage of monocytes and basophils (p=0.622, p=0.09, respectively). However, only the percentage and number of eosinophils had a correlation with the ΔFS score. Further multivariate analysis revealed a significant correlation between the disease duration, eosinophil count and percentage, and the disease progression rate (p<0.0001, p=0.048, p=0.023, respectively). The neutrophil to eosinophil ratio (NER), lymphocyte to eosinophil ratio (LER) and monocyte to eosinophil ratio (MER) were significantly lower in patients with ALS than in healthy controls. However, only the LER was significantly correlated with the ΔFS score. Conclusion: These observations implicate neutrophils, lymphocytes and eosinophils as important factors, and increasing eosinophils counts were negatively correlated with the ΔFS score in patients with ALS.